ATM 2016
DOI: 10.20937/atm.2016.29.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of pines in Mexico to temperature varies with age

Abstract: RESUMENMéxico tiene abundancia de especies de Pinus, con P. cooperi como especie dominante de gran importancia ecológica. En este estudio se comparó la sensibilidad climática de dos clases de edad de árboles de P. cooperi que crecen en la Sierra Madre Occidental: jóvenes (< 80 años) y maduros (≥ 80 años). Se desarrolló una curva regional de estandarización del crecimiento del ancho de anillo para las dos clases de edad. El análisis estadístico mostró que el crecimiento anual del ancho de anillo del árbol fue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…in northeast Hamburg of northern Germany, Pinus taiwanensis Hayata. in Taiwan, and Pinus cooperi Blanco in the Sierra Madre Occidental of northern Mexico [57][58][59][60]. As shown by a controlled experiment on cambial cell sensitivity to rising temperature of Cryptomeria japonica (L. f.) D. Don from different ages, the young tree growth trend would more easily be limited by long-term drought [61].…”
Section: Age-effect On Tree Radial Growthmentioning
confidence: 99%
“…in northeast Hamburg of northern Germany, Pinus taiwanensis Hayata. in Taiwan, and Pinus cooperi Blanco in the Sierra Madre Occidental of northern Mexico [57][58][59][60]. As shown by a controlled experiment on cambial cell sensitivity to rising temperature of Cryptomeria japonica (L. f.) D. Don from different ages, the young tree growth trend would more easily be limited by long-term drought [61].…”
Section: Age-effect On Tree Radial Growthmentioning
confidence: 99%
“…Recent articles have shown that long-term trends vary with stand age, which also affects the response to climate temperature, precipitation, and CO 2 [8,9]. On the other hand, eco-physiological processes may influence tree growth in relation to tree age, where the hydraulic limitation is one of the main physiological variables that explains why there are differences in the sensitivity of trees to climate at different age classes [10][11][12]. Concerning physiological reactions according to ontogeny, increases in atmospheric CO 2 and air temperature during the 20th century have been related to increments in the iWUE and the intercellular CO 2 concentration, with adult trees showing higher iWUE values than young trees, which broadly indicates the incidence of climatic, environmental, and ontogenetic variability in the tree responses [13].…”
Section: Introductionmentioning
confidence: 99%
“…Geographical distribution of species is not random [5], and their dispersal and adaptability depend on the intrinsic limitations of the species. In addition, these which could be accentuated by ecological and physiological aspects specific of these species, such as biological associations, growth rate, or the pollen and seeds dispersion [6,7], which aspects that can be drastically modified by changes in climatic conditions [1,8,9]. Moreover, to the complex interaction of limiting environmental factors as temperature or precipitation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has been suggested that if the climatic tolerance of a species is not extensive enough to face new environmental conditions, then those species with strong niche conservatism must migrate or become extinct [10,13]. Climate change could significantly accelerate the migration or potential reduction of forest populations [8,14,15], due to the alteration of regulatory variables such as temperature, precipitation or wind intensity [8,9]. Another important aspect is the genetic variability reduction of some populations, which limits their plasticity to adapt to new conditions [16,17,18] and then limit the survival of these species or their establishment at higher altitudes or northern latitudes [11,14].…”
Section: Introductionmentioning
confidence: 99%